Pengaruh Lingkungan Kerja, Kompetensi, Motivasi dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT. XYZ - Faridah Jane Quinta; Innocentius Bernarto (Universitas Sam Ratulangi, 2021)
The objectives of this study are to know: 1) Is work environment has a positive influence on employee performance, 2) Is competence has a positive influence on employee performance, 3) Is motivation has a positive influence on employee performance, and 4) Is job satisfaction has a positive influence towards employee performance. This study took 50 staff from XYZ company who were still actively working until May 30th. This study is using PLS-SEM (Partial Least Square – Structural Equation Modeling) for data processing. The finding of this study showed that the work environment has no positive influence on employee performance. This study also showed that competence, motivation, and job satisfaction have a positive influence on employee performance. This study can be used as input in the management of XYZ company to enhance their employee performance.